Escherichia coli from community-acquired urinary tract infections resistant to fluoroquinolones and extended-spectrum beta-lactams - Samuel Kariuki,1 Gunturu Revathi,2 John Corkill,3 John Kiiru,1 Joyce Mwituria,1Nazir Mirza,4 C. Anthony Hart.3 (The Journal of Infection in Developing Countries, 2007)
Background: Uropathogenic Escherichia coli are increasingly becoming resistant to flouroquinolones and to other commonly available antimicrobials. We sought to investigate the genetic basis for fluoroquinolone and extended spectrum beta-lactam (ESBL) resistance in 17 fluoroquinolone-resistant (MIC of levofloxacin and ciprofloxacin >32 µg/ml) E. coli isolated from patients with urinary tract infections (UTIs).Methods: We applied PCR and Pulsed Field Gel Electrophoresis (PFGE) to characterize resistance genes and to determine clonal relatedness of strains, respectively.Results: Twelve of the 17 E. coli were resistant to multiple drugs, including ampicillin, co-amoxyclav, cefotaxime, ceftriaxone, ceftazidime and gentamicin and nalidixic acid and produced plasmid-mediated CTX-M-15 type ESBLs and CMY-2 AmpC type enzymes. The other 5 E. coli that were non-ESBL-producing were multiply resistant to ampicillin, nitrofurantoin, cefoxitin, nalidixic acid. Resistance to fluoroquinolones resulted from a combination of the presence of qnrA, qnrB, ciprofloxacin acetylating enzyme designated aac(6')-1b-cr, and mutations in the two amino acid substitutions; 83 Serine (TCG) to Leucine (TTG) and 87 Aspartic acid (GAC) to Asparagine (AAC). Conclusion: Antibiogram patterns and PFGE of E. coli showed that these were community acquired UTI caused by pockets of clonally-related and some discreet strain types. Plasmid-mediated CTX-M-15 beta-lactamases and CMY-2 AmpC enzymes and fluoroquinolone resistant E. coli are becoming increasingly prevalent in hospitals in Kenya, posing a major challenge in the management of UTIs.